Analisis Kepuasan Mahasiswa MBKM terhadap Layanan E-Government ELSA BRIN - Azmi, Muhammad Nizar; Salsabila, Adinda (FIA Unkris Press, 2025)
E-Government services play a vital role in supporting academic and research activities in higher education, especially in the digital era that demands efficiency, accessibility, and transparency. ELSA BRIN (E-Layanan Sains BRIN) is a digital platform developed by the National Research and Innovation Agency (BRIN) to facilitate online access to research services for students, researchers, and the general public. This study aims to evaluate the satisfaction levels of university students participating in the Merdeka Belajar Kampus Merdeka (MBKM) program regarding their experiences with ELSA BRIN. A descriptive qualitative method was employed, with data collected through open-ended responses from 32 students who had utilized the platform during their research activities.The findings indicate that most students benefited from the fast response times, ease of access, and administrative support provided by the platform. However, several challenges were also identified, including technical disruptions, an imprecise location-based attendance feature, and a user interface that was difficult for new users to navigate. This study is unique in its focus on the user experience of MBKM participants, who represent a digitally literate academic demographic. The results suggest that the success of e-Government platforms in the research sector is not solely determined by technological sophistication but also by user satisfaction and usability. Recommendations include simplifying the user interface, improving service documentation, and enhancing the availability of responsive technical support to ensure broader and more effective adoption.